Molecular insights into impacts of EDTMPA on membrane fouling caused by transparent exopolymer particles (TEP) - Pan, Zhenxiang; Zeng, Bizhen; Yu, Genying; Lin, Hongjun; Hu, Lijiang; Teng, Jiaheng; Zhang, Hanmin; Yang, Lining (The Science of the total environment, 2022)
While ethylenediamine tetramethylenephosphonic acid (EDTMPA) has been emerged as a stronger chelating agent than ethylene diamine tetraacetic acid (EDTA) for fouling mitigation, and transparent exopolymer particles (TEP) is a major foulant in membrane-based water treatment process, effects of EDTMPA on TEP fouling and the underlying mechanism have been not yet studied. In this study, Flory-Huggins lattice theory was combined with density functional theory (DFT) technology to explore this subject at molecular level. Filtration experiments showed a unimodal pattern of specific filtration resistance (SFR) of TEP sample with Ca2+ concentration in range of 0–3 mM. For the TEP sample with the peak SFR value at 1.5 mM Ca2+, continuous addition of EDTMPA (from 0 to 100 mg·L−1) resulted in a sustained decrease in SFR. Energy dispersive spectroscopy (EDS) mapping characterization showed the continuing decline of calcium content in the TEP layer with increase of EDTMPA addition, indicating that EDTMPA successfully captured Ca2+ from alginate‑calcium ligation (TEP), and then disintegrated the TEP structure. DFT simulation showed that Ca2+ preferentially coordinated with the terminal carboxyl groups of alginate chains to form a coordination configuration that is conducive to stretch the three-dimensional polymer network. Such a network corresponded to an extremely high SFR according to Flory-Huggins theory. EDTMPA addition caused disintegration of the coordination configuration of Ca2+ binding to terminal carboxyl groups, which further resulted in collapse and flocculation of TEP gel network structure, thus leading to a continuous SFR decrease. This work provided deep thermodynamic insights into effects of EDTMPA on TEP-associated fouling at molecular level, facilitating to better understanding and mitigation of membrane fouling. [Display omitted] •EDTMPA reduced specific filtration resistance (SFR) of transparent exopolymer particles (TEP).•A unimodal SFR pattern of TEP formed from alginate at Ca2+ in range of 0–3 mM was observed.•Ca2+ preferentially coordinated with alginate terminal carboxyl groups, leading to high SFR.•EDTMP successfully disintegrated the TEP structure by capturing calcium ions, decreasing SFR.•This work provided thermodynamic molecular insights into effects of EDTMPA on TEP fouling.